The Political Influence Pattern of the "Eurasia Central Region"Based on Syria and Ukraine Events. (May 2022) - Zhao, Changping; Liu, Mengru; Gong, Yu; Hou, Yingying; Cao, Xuping
Due to geopolitical factors, Eurasia is at the center of gravity in international relations and has become the core area of the game of great powers. Focusing on the Syrian and Ukrainian issues, we conduct event research by looking for relevant literature and news materials, and organize and analyze the theme of international organization meetings dedicated to solving these two issues. By creating complex networks, we use quantitative data to analyze the geopolitical forces in central Eurasia and reflect the evolution of the political landscape in the region. We have found that: First, Eurasia is still the center of geopolitics in the world, and the status of land-powered countries will rise. Second, the geopolitical structure of the Eurasian center has begun to take shape as a quadrilateral relationship between the United States and its Asia-Pacific allies (Japan and Australia), the European Union, Russia, and China. Third, the political influence of the United States in Eurasia is declining and its hegemonic status is weakening. China's political influence has gradually increased, and Russia's geopolitical influence has declined significantly. The study, on the one hand, clarifies the evolution of the political landscape of the region and gives the reader a clear idea of the involvement of geopolitical forces. On the other hand, it provides some guidance for the future development of the Eurasian countries, especially China.